Isolable Stannenolates Enable the Synthesis of Visible‐Light Photoinitiators. Issue 3 (4th December 2021) - Maier, Janine; Müller, Stefanie M.; Torvisco, Ana; Glotz, Gabriel; Fischer, Roland C.; Griesser, Thomas; Kelterer, Anne‐Marie; Haas, Michael
Abstract: Isolable stannenolates LKSn[(CO)R]3 (R=2, 4, 6‐trimethylphenyl (1 a, b ), L=DME for (1 a ) or 18‐crown‐6 for (1 b )), a new building block for the synthesis of effective Sn‐based photoinitiators, were synthesized. The formation of these derivatives was confirmed by NMR spectroscopy, UV/Vis spectroscopy as well as X‐ray crystallographic analysis. Compound 1 a is employed as a synthon in main group chemistry through reactions with two different types of electrophiles (acid chlorides and alkyl halides). All investigated electrophiles react via the salt metathesis reaction and gave rise to novel acylstannanes in good to excellent yields. The applicability as visible light photoinitiators is demonstrated by photobleaching (UV/Vis absorption spectroscopic studies) as well as through application in photo‐DSC studies. Abstract : A convenient method is reported to obtain isolable triacylstannenolates in good yields. Besides the elucidation of the dominant resonance structure, these derivatives were used as new building blocks in organotin chemistry. Reaction with suitable electrophiles gave rise to the formation of a variety of new acylstannanes, which represent visible light tin‐based photoinitiators.